Emotion, mental and spiritual regulation of the higher education community during the COVID-19 pandemic - Syaidatun Nazirah Abu Zahrin; Rezki Perdani Sawai; Joki Perdani Sawai; Zaizul Ab Rahman; Mohamad Zaki Samsudin (Penerbit Universiti Kebangsaan Malaysia, 2021)
Higher education community faces a variety of challenges in teaching and learning following the imposition of the Movement Control Order (MCO) and post MCO during the COVID-19 pandemic. This study explains emotion, mental and spiritual regulation during COVID-19, and discusses the importance of emotion regulation in improving mental health. This study also provides the mechanisms to help individuals regulate their mental, emotional, and spiritual conditions post COVID-19. Emotional, mental, and spiritual regulation are important in overcoming the challenges during and following the COVID-19 pandemic. The findings of this study serve as a guidance for policy makers, leaders, academics, and higher education staff in preparing action plans and interventions to help individuals in regulating their emotion, mental and spiritual health following the foreseeable end of the COVID-19 pandemic. The conceptual understanding presented in this study forms the framework for future empirical research.